A Comparative Study of Local Dietary Intake Among Subjects with Hypertensive Disorders of Pregnancy Attending Antenatal Care - Chibuike F. Chukwunyere; David O. Awonuga; Taiwo Olunuga; Ifeoma C. Udenze (European Medical Journal, 2022)
Background: Hypertensive disorders of pregnancy remain among the most significant causes of pregnancy-related complications. The research by the Dietary Approaches to Stop Hypertension (DASH) group revealed that non-pharmacological measures and intervention such as diet can be used to control blood pressure. Objective: This study was completed to determine the frequency of consumption of local food among females who were pregnant and their relationship with pregnancy-related hypertensive disorders. Methods: This was a descriptive research study of females who were pregnant with pre-eclampsia (PE) and gestational hypertension (GH) who presented at the Federal Medical Centre (FMC), Abeokuta, Nigeria. During the study period (September-October 2019) at the tertiary healthcare centre, 45 subjects who were pregnant were select from a PE and GH group, and matched with 45 patients with normotension. Comparison of bean meal onsumption (gbegiri) and bone meal (gbure-oloboro) consumption in subjects who were pregnant did not reveal statistically significant differences in those with PE and GH. Results: The findings reveal a statistically significant difference in milk consumption between females who were pregnant with mild and severe PE (p=0.019). There was also a statistically significant difference in subjects with mild and severe GH who consumed milk (p=0.003).